Immunoexpression of angiogenesis and proliferation markers in patients treated with cyclosporin A - Afonso, M. [UNESP]; Perrotti, V.; Rapani, M.; Iaculli, F.; Piccirilli, M.; Onuma, T.; Shibli, J. A.; Oliveira Bello, V. de; Sposto, M. R.; Artese, L. (Minerva Medica, 2014)
In the present immunohistochemical study, the expression of vascular endothelial growth factor, nitric oxide synthase 1 and 3, and Ki-67 in the gingival tissues of renal transplant patients treated with cyclosporin A was assessed. Gingival overgrowth (GO) frequently occurs in transplant patients receiving immunosuppressive drugs such as cyclosporine and this gingival inflammation might play an important role in the pathogenesis of drug-induced GO. Twenty-eight human gingival biopsies were taken from healthy patients with chronic periodontitis (N.=14 control group), and from renal transplant recipients treated with cyclosporin A (N.=14 test group). The retrieved specimens were immunohistochemically processed and stained for vascular endothelial growth factor, nitric oxide synthase 1 and 3, and Ki-67. The levels of vascular endothelial growth factor, nitric oxide synthase 1 and 3, and Ki-67 were found to be significantly different among groups (P>0.001), with patients treated with cyclosporin A showing higher levels of all the analyzed markers compared to control group. In summary, the data from this pilot study suggests that the investigated factors have a role in the inflammation processes associated to immunosuppressive therapy. However, further studies with a larger sample population need to be conducted for an exhaustive knowledge of the mechanisms leading to GO.